Uneven distribution in energy conservation services through performance contracts in China - Zheng, S; Zhai, H; Hsu, S-C; Armanios, DE (Elsevier, 2024)
Energy performance contracting is increasingly employed to promote energy conservation toward sustainable development. This study characterizes these services in China through an analysis from 2011 to 2020 that reveals imbalances in the energy services company (ESCO) sector with respect to trade route, customer base, and energy conservation technology. More specifically, analyses of inter- and intra-province trade networks show that Beijing was the lead provider of ESCO projects, whereas Hebei was the lead customer. Jiangsu, Liaoning, and Inner Mongolia have risen to be new significant players during the 13th Five Year Plan (FYP) period (2016–2020). Although a wide range of energy conservation measures were deployed, ESCO projects were most prevalent in the industrial sector, with particular emphasis on residual heat, pressure and gas recovery. However, the building sector become an increased focus for ESCO projects during the 13th FYP. We further find that national guidelines alone may not lead to significant advances in energy conservation without additional and complementary provincial support. Such heterogeneity, especially at the provincial level, may help explain observed imbalances in ESCO projects. While prior studies usually focus on national guidelines, the more general implication and call of our study is that greater attention should be placed on subnational (provincial) guidelines around energy conservation.